Apprenticeship and Youth Unemployment - Pierre Cahuc; Jeremy Hervelin (Institute of Labor Economics (IZA), 2020)
In France, two years after school completion and getting the same diploma, the employment rate of apprentices is about 15 percentage points higher than that of vocational students. Despite this difference, this paper shows that there is almost no difference between the probability of getting a callback from employers for unemployed youth formerly either apprentices or vocational students. This result indicates that the higher employment rate of apprentices does not rely, in the French context, on better job access of those who do not remain in their training firms. The estimation of a job search and matching model shows that the expansion of apprenticeship has very limited effects on youth unemployment if this is not accompanied by an increase in the retention of apprentices in their training firm.
Keywords: J24; M53; M51; 330; field experiment; school-to-work transitions; apprenticeship